Accessibility and Inclusion of Students with Disabilities in University of Dhaka: Transforming the University in Line with Sustainable Development Goals (Teacher’s World: Journal of Education and Research, 2024)
This study aimed to explore what constitutes an accessible and supportive environment for promoting inclusive education for all students with a particular focus on students with disabilities (SWDs) aligning with the plea of SDGs in the University of Dhaka. Thus, the general objective was to come up with a holistic understanding of inclusive education practices by comprehensive analysis of features related to accessibility, reasonable accommodation and Universal Design for Learning (UDL) for SWDs, also of exploring the scopes, limitations and challenges prevalent in the process. The objectives of the study required both confirmatory and exploratory approaches, thus demanding to adopt a mixed-method research approach that allowed researchers to choose a flexible ‘within- stage-mixed model design’ with emphasis on qualitative approaches of data collection and analysis. Semi-structured interview schedule as data collection instrument yielded qualitative data that was analyzed using descriptive and thematic analysis framework (Braun & Clarke, 2006). The findings shed light on the existing scopes, limitations and challenges in the learning environment of the university in addressing the learning needs of SWDs. The findings also produced valuable information for transforming University of Dhaka towards a recognized disable-friendly university with an impact ranking, as well as with a QS Star University Rating on Inclusiveness.Teacher’s World: Journal of Education and Research, 49 (1), 205-225